Global implementation of the world health organization's International Classification of Diseases (ICD)‐11: The allergic and hypersensitivity conditions model. Issue 9 (14th July 2020) - Tanno, Luciana Kase; Chalmers, Robert; Jacob, Robert; Kostanjsek, Nenad; Bierrenbach, Ana Luiza; Martin, Bryan; Molinari, Nicolas; Annesi‐Maesano, Isabella; Papadopoulos, Nikolaos G.; Sanchez‐Borges, Mario; Rosenwasser, Lanny J.; Ansontegui, Ignacio; et al.
Abstract: The International Classification of Diseases (ICD) provides a common language for use worldwide as a diagnostic and classification tool for epidemiology, clinical purposes and health management. Since its first edition, the ICD has maintained a framework distributing conditions according to topography, with the result that some complex conditions, such as allergies and hypersensitivity disorders (A/H) including anaphylaxis, have been poorly represented. The change in hierarchy in ICD‐11 permitted the construction of the pioneer section addressed to A/H, which may result in more accurate mortality and morbidity statistics, including more accurate accounting for mortality due to anaphylaxis, strengthen classification, terminology and definitions. The ICD‐11 was presented and adopted by the 72nd World Health Assembly in May 2019, and the implementation is ongoing worldwide. We here present the outcomes from an online survey undertaken to reach out the allergy community worldwide in order to peer review the terminology, classification and definitions of A/H introduced into ICD‐11 and to support their global implementation. Data are presented here for 406 respondents from 74 countries. All of the subsections of the new A/H section of the ICD‐11 had been considered with good accuracy by the majority of respondents. We believe that, in addition to help during the implementation phase, all the comments provided will help to improve the A/H classification and to increase awareness by different disciplines of what actions are needed to ensure more accurate epidemiological data and better clinical management of A/H patients.